2021
DOI: 10.3390/cells10051021
|View full text |Cite
|
Sign up to set email alerts
|

Role of the TRP Channels in Pancreatic Ductal Adenocarcinoma Development and Progression

Abstract: The transient receptor potential channels (TRPs) have been related to several different physiologies that range from a role in sensory physiology (including thermo- and osmosensation) to a role in some pathologies like cancer. The great diversity of functions performed by these channels is represented by nine sub-families that constitute the TRP channel superfamily. From the mid-2000s, several reports have shown the potential role of the TRP channels in cancers of multiple origin. The pancreatic cancer is one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 115 publications
0
10
0
Order By: Relevance
“…In conclusion, all of these results consistently point towards some family members being important players in the tumorigenic process: TRPM8 , TRPM7 , TRPV6 , and TRPA1 [ 11 ]. Only recently has a study using the gene set enrichment analysis (GSEA) shown that two members of the TRPC subfamily ( TRPC3 and TRPC7 ) possess clinical predictive value for PDAC.…”
Section: Introductionmentioning
confidence: 89%
“…In conclusion, all of these results consistently point towards some family members being important players in the tumorigenic process: TRPM8 , TRPM7 , TRPV6 , and TRPA1 [ 11 ]. Only recently has a study using the gene set enrichment analysis (GSEA) shown that two members of the TRPC subfamily ( TRPC3 and TRPC7 ) possess clinical predictive value for PDAC.…”
Section: Introductionmentioning
confidence: 89%
“…Transient Receptor Potential (TRP) channels are a family of nonselective ion channels mediating various physiological functions in many cell types. These channels have recently been identified as critical regulators of pancreatic cancer cell proliferation, invasion, and metastasis [ 4 , 5 , 6 , 7 ]. Targeting TRP channels represents an exciting new strategy for inhibiting pancreatic cancer cell growth and survival.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the development of effective treatment methods for pancreatic cancer has been hindered by the lack of understanding of the pathogenesis, partly due to the difficulty in studying human tissue samples. Despite this, scientific research on this topic has witnessed steady development in the past few years in understanding the molecular mechanisms that underlie TRP channel disturbance [ 4 , 5 , 6 , 7 ]. The focus is on exploring the pathogenesis of pancreatic cancer and its related pathways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TRPs are discussed to be important mediators of pain and are under current investigation as targets for developing new pain medications [ 12 ]. In addition to the role of maintaining tissue homeostasis, some previous reports link malignant disease progression with responses of these channels including for PAAD [ 13 ]. However, to our knowledge the relevance of TRP from a translational viewpoint, interrogating NGS data of patient material and clinical course, has been not been assessed.…”
Section: Introductionmentioning
confidence: 99%